Karakteristik Fisikokimia Dan Daya Terima Es Krim Dengan Penambahan Buah Raspberry (Rubus Rosifolius) - Suciati, Fitri; Wahyuni, Anggi Sri; Rahayu, Wiwik Endah (Universitas Gajah Putih, 2023)
Ice cream is a dairy product made through freezing process that has high nutrition. Processing of ice cream can be varied by adding various kind of fruits, one of which is by using raspberries. The purpose of this final project was to determine the effect of raspberry addition on physicochemical properties and acceptability of ice cream. The design used was a Completely Randomized Design (CRD) consisting of 3 treatments with raspberry fruit concentration P0 = 0%, P1 = 20%, P2 = 40% with 3 replications. The parameters tested were overrun, melting power, pH, vitamin C and acceptability. The data obtained by physical and chemical tests were then analyzed using the ANOVA ( Analysis of Variance ) test, followed by the DMRT ( Duncan Multiple Range Test ) test with a significant level of 5% while the hedonic test used statistical analysis of mode values. The test results on physicochemical characteristics showed that the addition of raspberries had a significant effect (P<0.05) on overrun, pH and vitamin C, but did not have a significant effect (P<0.05) on the melting power of ice cream. The most preferred ice cream and the best concentration in the P2 treatment with the addition of 40% raspberry fruit with an overrun value of 79.65%, melting power with 12.09 minutes, pH value of 5.51 and vitamin C of 0.94 mg/ g.